Can internal control components influence internal customer satisfaction? An applied study in a shared service centre / Kamaruzzaman Muhammad ... [et al.] - Muhammad, Kamaruzzaman; Mohd Rafi, Ridzuan Hashim; Ghani, Erlane K; Sukmadilaga, Citra (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study examined whether internal control components can influence internal customer satisfaction in a shared service centre of a company in Malaysia. Specifically, five internal control components based on the COSO framework were chosen: control environment, risk assessment, control activities, information and communication, and monitoring. Using a questionnaire survey of employees of a shared service centre, the results showed that three internal control components influenced internal customer satisfaction. The three internal control components were risk assessment, control activities, and information and communication. However, this study showed that control environment and monitoring did not influence internal customer satisfaction. The findings implied that more attention should be given to risk assessment, control activities, information, and communication in order to ensure that the service quality provided by the shared service centre can be maintained or improved to increase the satisfaction of internal customers. The findings study can shed some light on the factors that can influence the performance of shared service centres, which in this study are the internal control components. In addition, the findings in this study add additional findings to the literature on internal control components and internal customer satisfaction, particularly in shared service centres.